"Problemas comportamentales y emocionales" en niños de 6 a 11 años: una revisión (2020)
Systematic reviews (SR) are a documentary research tool that provides valuable and accurate information about different constructs and variables quickly and specifically. For other side, the emotional and behavioral problems (PE&PB) have shown to have a large body of current literature, however, filtering and analyzing it under very specific criteria is a task that is not carried out frequently, for this reason the present project sought to analyze and to describe the research published between 2010 and 2019 on the status and quality of the variable emotional and behavioral problems in children from 6 to 11 years old through three major metasearch engines (Ebsco, Web Science and PubMed). For this, the guidelines for the creation of SRs proposed by PRISMA and the SIGN criteria were followed; the results analyze 34 articles considered as suitable; The state (countries that provide the most literature, the predominant language, designs preferred by the authors, years of greater publication and more frequent constructs with which the PE&PB are studied) and finally the quality of the literature are discussed in light of the literature. Academic found (Level of evidence and degree of recommendation).